Novel DBMBF2-BODIPY dyads connected via a flexible linker: synthesis and photophysical properties. (16th June 2022) - Kononevich, Yuriy N.; Belova, Anastasia S.; Ionov, Dmitry S.; Sazhnikov, Viacheslav A.; Pakhomov, Alexey A.; Alfimov, Mikhail V.; Muzafarov, Aziz M.
Abstract : Novel BODIPY and DBMBF2 dyads connected via a flexible trisiloxane linker were synthesized and their photophysical properties were investigated. Abstract : Novel boron dipyrromethene (BODIPY) and dibenzoylmethanatoboron difluoride (DBMBF2 ) dyads connected via a flexible trisiloxane linker were synthesized and their photophysical properties were investigated. The emission of the dyads is characterized by large pseudo-Stokes' shifts (up to 7712 cm −1 /143 nm). It was shown that an efficient Förster resonance energy transfer (ET efficiency up to 98%) is observed in these systems, dissolved in various solvents of different polarities. The quantum yields of fluorescence of the dyads are lower than those obtained for the model BODIPY molecule due to the complex interaction between the fluorophore fragments, due to the presence of the flexible linker. It was found that after the excitation of the DBMBF2 unit subsequent energy transfer to the BODIPY fragment, mutual rearrangement of BODIPY and DBMBF2 units and the formation of an intramolecular complex are possible.